(untitled) (International Journal of Current Engineering and Technology, 2015)
Multiphase Variable-speed motor drivers have substantially grown with the advancement in power electronics in the beginning of this century. Reference frame theory concept is used for analysis & performance of five phase induction machine. Traditionally three phase supply is produced and therefore Multiphase inverter is used to provide multiphase supply for multiphase supply. Simulation model of five phase induction machine in dqxyo axis based on mathematical modeling & it’s controlling using V/f Control Technique is modeled using simpower system block-set of Matlab/simulink. Spwm Technique is used to generate the pulses for the inverter.